2018
DOI: 10.31873/ijetr.8.11.87
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Transient Response of a DC Motor Controller Based on Non-Linear Optimization Techniques

Abstract: In this study, various precise and appropriate control systems that use a DC motor, have been simulated for improved transient response. Three controllers: lead-lag compensator, conventional Proportional-Integral-Derivative (PID) and Fuzzy logic controller were designed and simulated in order to analyse the performance. Among them, Fuzzy logic algorithm tuning for PID controller exhibits better transient response for DC motor actuators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…179 in [1] and, which is one and the same, in task 16.36 [2]). An analysis of works [3][4][5][6][7][8][9][10][11][12][13][14][15][16] showed that the geared linkage mechanism (according to N.E. Zhukovsky, "as a crank") pivotally connected to the satellite of the planetary mechanism of the two-wire Assur group of the second kind is not known at all, except in [14] ( fig.…”
Section: Introductionmentioning
confidence: 99%
“…179 in [1] and, which is one and the same, in task 16.36 [2]). An analysis of works [3][4][5][6][7][8][9][10][11][12][13][14][15][16] showed that the geared linkage mechanism (according to N.E. Zhukovsky, "as a crank") pivotally connected to the satellite of the planetary mechanism of the two-wire Assur group of the second kind is not known at all, except in [14] ( fig.…”
Section: Introductionmentioning
confidence: 99%